Scar Endometriosis-A Case Report - DAPHNE FONSECA,; ANIL ANGELO FONSECA,; S M AHALYA, (International Journal of Pharma and Bio Sciences, 2012)
Endometriosis is a fairly common disease found in a variety of extrauterine locations. It primarily affects reproductive age women and has symptoms varying from occult to more specific complaints. Occasionally the lesions produce solid nodules and/or cysts that are clinically palpable and easily evaluated by fine needle aspiration (FNA).We describe a case of endometriosis diagnosed by FNAC and confirmed by histopathology. Our patient was a multiparous woman who had undergone Caesarean section 5 years back and developed a palpable swelling under the suture line which was clinically diagnosed as desmoid tumor.Endometriotic nodules must be evaluated for possible malignant transformation and differentiated from other benign and malignant masses, especially when clinical symptoms are vague..